(3GdJjSjQ aj GdeOGhGI hGdJOHjQs - (3YHO Gdedc Hf RgQ Hf YHO Gdedc, CHh eQhGf,J (B557 (3g` s
(3ChdgG (B:s
(3Efi hGdTGgO Gddg de CVY gPG GdcJGH EdG hbO dRfi GdEVWQGQ dTOI GdYRe s
(3BNQgG (B:s
(3hEPG bO CJjJ ef Gdbhd eG CQOJ EJjGfg aCfG bGWY Gdbhd EP bO GSJeeJg hHGddg GdJhajb Je cJGH GdJjSjQ ai GdeOGhGI hGdJOHjQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B303s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs